Microfabrication and characterisation of thin films on rigid and flexible substrates - Tan, Justin Yang Yeh (Nanyang Technological University, 2022)
Investigation was carried out to determine optimal parameters suitable to produce patterned thin films on rigid and flexible substrates. Characterisation studies were performed on the films produced. The processes selected were based on having a low cost and being highly scalable. The report details the iterative process of developing a reliable thin film production process and the challenges faced. Two different steps in thin film production, namely deposition and patterning of thin films. Fe-Ni alloy was used as the primary deposition material by means of electrochemical and electroless deposition methods. To pattern thin films, maskless laser interference lithography was used. In the production of thin films on rigid substrates, the use of copper plate and silicon wafer substrates were investigated. Copper foil, polyethylene terephthalate (PET) film and graphite sheets were used as flexible substrates. Characterisation criteria of the thin films during deposition include percentage of Fe deposited, grain size, deposition thickness and growth rate. In patterning experiments, parameters explored consist of the various baking times needed, exposure time, double and triple exposure, and lithography performed on flexible substrates. Further steps that may be taken in thin film production apart from deposition and patterning are discussed and will be carried out by future work.